Cross-continental phylogeography of two Holarctic Nymphalid butterflies, Boloria eunomia and Boloria selene - Maresova, Jana; Habel, Jan Christian; Neve, Gabriel; Sielezniew, Marcin; Bartonova, Alena; Kostro-Ambroziak, Agata; Fric, Zdenek Faltynek (PloS one, 2019)
Pleistocene glaciations had significant effects on the distribution and evolution of species inhabiting the Holarctic region. Phylogeographic studies concerning the entire region are still rare. Here, we compared global phylogeographic patterns of one boreo-montane and one boreo-temperate butterflies with largely overlapping distribution ranges across the Northern Hemisphere, but with different levels of range fragmentation and food specialization. We reconstructed the global phylogeographic history of the boreo-montane specialist Boloria eunomia (n = 223) and of the boreo-temperate generalist Boloria selene (n = 106) based on mitochondrial and nuclear DNA markers, and with species distribution modelling (SDM). According to the genetic structures obtained, both species show a Siberian origin and considerable split among populations from Nearctic and Palaearctic regions. According to SDMs and molecular data, both butterflies could inhabit vast areas during the moderate glacials. In the case of B. selene, high haplotype diversity and low geographic structure suggest long-lasting interconnected gene flow among populations. A stronger geographic structuring between populations was identified in the specialist B. eunomia, presumably due to the less widespread, heterogeneously distributed food resources, associated with cooler and more humid climatic conditions. Populations of both species show opposite patterns across major parts of North America and in the case of B. eunomia also across Asia. Our data underline the relevance to cover entire distribution ranges to reconstruct the correct phylogeographic history of species.
Keywords: Animals; argininkinasa; Genetic Variation; Arginine Kinase; zvířata; respirační komplex IV; Butterflies; Phylogeography; Electron Transport Complex IV; genetická variace; fylogeografie; motýli